THE USE OF VOCABULARY JOURNAL IN ENRICHING STUDENTS’ VOCABULARY MASTERY AND THE STUDENTS’ ATTITUDES TOWARD ITS USE - Fika Nurul Hanifia (Journal of English and Education, 2013)
The research was aimed at discoveringthe effects of vocabulary journal on the students’ vocabulary mastery and also their attitudes toward its application in the class. This research employed quasi-experimental design. Fifty students of eighth grade of a Junior High School in Bandung were taken and divided into two groups namely control group and experimental group. The data were gained from pre-test, post-test, and interview. The data of the pre-test and the post-test were analyzed using t-test while the data of the interview were analyzed descriptively. The result of the post-test showed the sig. (2-tailed) .000, which meant that after the treatment, both classes were different in terms of vocabulary score statistically. Experimental class tended to have better scores than control class did. Moreover, the data of the interview showed positive responses to the use of vocabulary journal in learning vocabulary. In summary, it was proven that to some extents vocabulary journal is effective to develop students’ ability in mastering vocabularies. Keywords: Students’ attitudes, Vocabulary journal, Vocabulary mastery